Expectations for Renewable Energy, and Its Impacts on Quality of Life in European Union Countries - Rosak-Szyrocka Joanna; Allahham Almuhannad; Żywiołek Justyna; Turi Jamshid Ali; Das Anupam (Management Systems in Production Engineering, 2023)
The primary goals of the study are to present a qualitative examination of household awareness of renewable energy sources and to ascertain their requirements, as well as their expectations for an improvement in quality of life as a consequence of using renewable energy to reduce greenhouse gas emissions and air pollution while improving public health. There are no empirical studies examining the level of household awareness of renewable energy in EU countries, so this gap is also considered a further area of empirical research. Seven European nations were selected for the study: the Czech Republic, Slovenia, France, Portugal, Spain, Austria, and Germany. The survey was conducted from April 2021 to June 2022 with over 17030 respondents. Additionally, it was given a statistical analysis by using the C-Pearson coefficient. Results of our study showed that households’ awareness is low and they also expect that they will not pay more for tourist services that use renewable energy sources. Moreover, results showed that when renewable energy sources are used, in households’ opinions, levels of CO2 will decrease and that this will have a favorable effect on the environment, but they still think that this will have a detrimental influence on their health.